Implementation of interactive HOTS e-modules based on gamification in improving learning outcomes in Islamic religious education subjects for students of SMPN 1 Taluditi - Darmawati Darmawati; Muliani Muliani (Universitas Muhammadiyah Enrekang, 2025)
The purpose of this study is to develop HOTS content in the e-module of Islamic Religious Education subjects at SMPN 1 Taluditi, increase creativity in developing teaching strategies and methods, improve critical thinking in understanding learning content and develop teacher creativity in designing materials, media and teaching modules that are appropriate to the conditions and abilities of students at the junior high school level. The method used is R&D with the DDDE (Decide, Design, Develop, and Evaluate) model which was chosen because it is in accordance with the objectives of developing HOTS and gamification-based interactive e-modules. A small-scale trial of the HOTS e-module was conducted by teacher experts and lecturers, and a large-scale trial was conducted by 22 students. The trial subjects were determined using a purposive sampling technique. Research data collection was carried out by administering a questionnaire test that had been collected descriptively. The results of the study showed that the gamification-based interactive HOTS e-module developed using the DDD-E model met the validity criteria with an average score of 3.89, was considered practical with an average score of 3.67, and demonstrated effectiveness, with 87.8% of students achieving a minimum test score of 70.